Acute Promyelocytic Leukemia - Sah, Kailash Prasad; Bhattarai, Susan (Journal of Nepal Paediatric Society, 2018)
Acute promyelocytic leukemia (APL) is the most malignant form of acute leukemia, relatively uncommon in children, rapidly fatal if untreated and several developments have paved the way to make this disease curable. We report a first case to our knowledge in Nepal, a 12 years old boy who was diagnosed as APL and treated with vesanoid 14 years back and has been free from disease till date.